Integration Dynamics Modified Homo Sapiens Psyche and Agi (Part 2) - Kruglov, A. G; Kruglov, A. A. (Transactions on Engineering and Computing Sciences, 2025)
The evolutionary dynamics of Homo Sapiens (HS), modifying the psyche, periodically transforms the structure of society and its relationship with the environment. The cumulative effect of HS psyche modification induces the bifurcation transformations of evolution. In searching for and finding optimal forms of adaptation, the HS psyche transforms changes in environmental parameters into cognitively consistent and agreed forms of symmetrical reflection in the psyche. "Consistency" requires periodic status correction to maintain the information balance of the system: object/reflection. Increasing virtuality modifies the HS psyche as it adapts to changing environmental parameters without engaging its conscious levels. The observed changes in the HS psyche highly likely converge with the constructive principles of mild autism spectrum disorders. Mildly autistic and innovative creative individuals form constructive cells/hubs of virtual space, creating an integral virtual society of cellular topology. What develops is a deep symbiotic relationship that morph into an endosymbiotic system stemming from the synergy of interacting systems: a society of cellular topology / information universe / artificial intelligence arsenal. The development dynamics of this synergistic endosymbiotic system generate a scalable structure that is structurally and functionally integral to the artificial general intelligence. The HS population in this structure becomes an AGI segment.